Análise da rotulagem nutricional de biscoitos sem glúten - ABREU, Alan Kardec da Silveira (2023)
Objective: To analyze the nutritional information contained in labels of glutenfree cookies. Method: The survey was carried out during the month of January 2019 in specialized specifications of the city of Belém, as well as on the internet. Information on calories, carbohydrate, protein, fat (total, saturated and trans), fiber and sodium were produced for 142 glutenfree products, organized into 12 categories: starch; sweet sequilho; wafer; cookie; candy; stuffed; cookie; integral of the cookie; donut; grissini; salty and rice. Descriptive statistics (mean, deviation and variation coefficient) were applied to the data. Results: There were large variations in the content of macronutrients between and within the categories, as variations found were 43.3 g / 100 g to 94 g / 100 g for carbohydrates; 0g / 100g to 16.4g / 100g for as proteins; 0g / 100g to 18.3g / 100g for saturated fat; 0mg / 100g to 1410mg / 100g for sodium and 0g / 100g to 16g / 100g for fiber. Conclusion: Although the products are in the same category, very different values of nutrients can be found, being essential, for the choice of the product in face of the individual needs, the reading of the nutritional information. In addition, in the “cracker” and “powder” categories, the sodium content needed to be reassessed, with reduction targets.